The Influence of Work Motivation and Organizational Citizenship Behavior on Employee Performance in The Rural Bank (BPR) in Bali, Indonesia - Suryani, Ni Kadek; Supartha, Wayan Gede; Saraswaty, Amrita Nugraheni; Wendikasari, Luh Ade Calista Sandy (Jurnal Manajemen Teknologi, 2025)
Abstract. The aims of this study is to examine the antecedents of rural bank (BPR) employees' performance in Bali province, Indonesia. Data collected through the use of the questionnaire. Research respondents were 65 people from all BPR Operational Section Heads who used it as a saturated sample. The SEM PLS analysis was performed to investigate the variables of employees motivation, organizational citizenship behaviour (OCB), and employee productivity. The result of the analysis showed that all hypotheses tested were significantly positively related. Through this study, it can conclude that employee performance in the banking sector supported by work motivation and OCB. These indicate the performance of BPR employees. It is necessary to strengthen the variable of work motivation and the OCB itself. Mediation study revealed that the OCB variable mediated the influence of job motivation on employee performance in a positive and significant manner. These suggest that while motivation for working and OCB grows, employee productivity in BPRs in Badung Regency and the city of Denpasar, Bali correspondingly increases. Keywords: Employee performance, organizational citizenship behavior, work motivation